Synergistic Cytotoxic Effect of Apis Mellifera syriaca Venom and Jania rubens Polysaccharide Extract on HCT-116 and HT-29 Colon Cancer Cell Lines - Rifi, Mariam; Tajer, Layla; Dassouki, Zeina; El-Obeid, Dany; Roufayel, Rabih; Fajloun, Ziad; Mawlawi, Hiba (Natural Products Journal, The, 2026)
IntroductionCombining multiple natural extracts may provide an additive and/or synergistic effect, increasing the anti-cancer potential of the formulation while aiding in the search for targeted chemical compounds for cancer treatment.MethodsHere, we confirmed the individual in vitro anti-proliferation effect of Apis mellifera syriaca bee venom (BV) and Jania rubens red algae polysaccharide extract (PE) on HCT-116 and HT-29 colon cancer cell lines and explored the synergistic effect of these two natural extracts, aiming to develop a new mixture with promising potential against colorectal cancer.Results and DiscussionGiven that the synergy between BV and algal PE was evaluated using concentrations of 5 and 250 μg/mL, respectively, a significant combined effect was noted, leading to at least a 20% more reduction in cell viability than with either extract alone. Additionally, the combination therapy significantly reduced cell migration more than either extract achieved on its own, exhibiting increased anti-migratory capability in a time-dependent manner.ConclusionThis synergy indicates the potential of enhanced anti-cancer efficacy in formulations based on combinations of natural components.
Keywords: algal extract